Exploring urban institutional pressures on logistics service providers. Issue 2 (7th March 2016) - Rose, William J; Mollenkopf, Diane A; Autry, Chad W.; Bell, John E.
Abstract : Purpose: – As global populations become increasingly urbanized and urban areas grow in density and complexity, many firms seeking to operate in these areas face significant new challenges. The purpose of this paper is to identify the approaches utilized by urban logistics service providers to overcome the issues resulting from urban density and complexity. The paper also identifies potential directions for future research based on the research findings. Design/methodology/approach: – The study followed a grounded theory approach (Corbin and Strauss, 2008) to uncover the approaches utilized by logistics service providers to adapt to urban environments. Findings: – The urban environment exerts certain coercive and mimetic pressures on logistics service providers. To overcome these pressures, urban logistics service providers seek to manage space, resources, and legitimacy in the urban environment. Research limitations/implications: – This research followed an inductive approach, and therefore, further empirical research is required to ensure statistical generalizability. Additionally, all research participants are currently employed in the USA, and so further research at the international level should be conducted. Practical implications: – The framework presented will enable firms seeking to enter the urban market to more quickly adapt to the specific pressures of the urban ecology. Originality/value: – While literature from several academic disciplines outline problems and solutions specific to urban areas, little qualitative, inductive research has been conducted in the field of urban logistics. The current research serves as a starting point for further urban logistics research.